Study on setting up the standard for tea leaves in processing of green tea powder of high quality - Thanh Mai, Nguyen Thi; Tram, Tran Bao; Chien, Truong Thi; Vinh, Doan The (Academia Journal of Biology, 2012)
Up to 2009, in Vietnam the nationwide area of tea planting reached 128.1 thousand hectares with the yield of 798.8 thousand tons of fresh tea buds. However, the exported tea value of Vietnamese tea has been still of moderate level in comparision with other countries due to low quality, numerous defects and excess amount of toxic residue resulted misuse of autumn using incontrollable pesticides and chemical fertilizer as well as of polluted water supply. The common varieties of tea planted at present are Camellia sinensis var. macrophylla, Camellia sinensis var. shan, PH1, TRI 777, LDP1, 1A, LDP2... One of the products from tea is green tea powder which is used more and more in food industry nowadays. The quality of the processed tea powder largely depends on the quality of fresh tea leaves. Therefore we carried out this study to set up the standard for tea leaves grown in the Northern area of Vietnam in order to obtain green tea powder of high quality. Samples of fresh tea leaves collected in various seasons of the year in Thai Nguyen, Moc Chau and Phu Tho provinces. The result of analysing samples of fresh tea leaves collected in showed that the tea leaves harvested in summer and autumn seasons from Moc Chau area have had the highest content of water, dissoluble substances, polyphenols and tanin. Based on results obtained we defined that standard for tea leaves of good quality is that the bud having three tender leaves harvested in the early morning with natural green colour, and the water content higher 70% (in natural weight), dissoluble substances from 40 to 45%, polyphenols higher 15% and tanin from 20 to 24% (dry weight).